Expert System for Diagnosing Diseases in Cats Using the Forward Chaining Method - Edward Robinson Siagian; Ibrahim; Ade Sarah Huzaifah (Cattleya Darmaya Fortuna, 2023)
An expert system for diseases in cats is an application that aims to helps in diagnosing disease in cats based on its symptoms and signs observed. The forward chaining method is used in this system to collect information from users, apply existing rules, and reach a final diagnosis. In this method, the expert system will start with the information provided by the user or results of observations, and use existing rules to reach conclusions or final diagnosis. The main steps in the forward chaining method include collection information, activating rules, evaluating conditions, and iterating until a final diagnosis is reached.While these methods can provide initial advice in diagnosing feline diseases, it is important to remember that expert systems are no substitute for a comprehensive medical assessment by a qualified veterinarian.